A systematic review of personality and musculoskeletal disorders: evidence from general population studies - Quirk, Shae E.; Koivumaa-Honkanen, Heli; Honkanen, Risto J.; Mohebbi, Mohammadreza; Stuart, Amanda L.; Heikkinen, Jeremi; Williams, Lana J. (Frontiers in Psychiatry, 2024)
Introduction We conducted a systematic review to evaluate the quality and extent of evidence on associations between personality disorders (PDs) and musculoskeletal disorders (MSDs) in population-based studies, since these disorders are leading causes of disease burden worldwide. Methods A search strategy of published, peer-reviewed and gray literature was developed in consultation with a liaison librarian and implemented for Embase, CINAHL Complete, Medline Complete, and PsycINFO via the EBSCOhost platform from 1990 to the present and CORDIS and ProQuest Dissertations & Theses Global, respectively. The inclusion criteria were as follows: I) general population participants aged ≥15 years; II) self-report, probable PD based on positive screen, or threshold PD according to the DSM-IV/5 (groupings: any, Clusters A/B/C, specific PD) or ICD-10/11; III) MSDs identified by self-report or ICD criteria (arthritis, back/neck conditions, fibromyalgia, osteopenia/osteoporosis) and III) cohort, case-control, and cross-sectional study designs. Two reviewers independently screened articles and extracted the data. Critical appraisal was undertaken using the Joanna Briggs Institute checklists for systematic reviews of etiology and risk. A descriptive synthesis presents the characteristics of included studies, critical appraisal results, and descriptions of the main findings. This review adhered to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Results There were 11 peer-reviewed, published articles included in this review (n = 9 cross-sectional and n = 2 case-control studies); participants were ≥18 years in these studies. No published gray literature was identified. Semi-structured interviews were the most common method to ascertain PDs; all studies utilized self-reported measures to identify MSDs. Overall, we detected limited and conflicting evidence for associations between PDs and MSDs. Discussion The main result may be explained by lack of population-based longitudinal evidence, heterogenous groupings of PD, and few comparable cross-sectional and case-control studies. Strengths of the review include a comprehensive search strategy and a discussion of mechanisms underlying possible associations between PDs and MSDs. Conclusions The quality of most studies included in this review that examined associations between PD and MSDs in general population adults was high. However, the results demonstrated limited and conflicting evidence for these associations, in part, due to lack of comparable evidence, which should be addressed in future research. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42021243094.